Understanding online learning across cultures: The encounter between Confucius culture and Western culture - Kang, Haijun (My University, 2014)
The purpose of this study is to understand how much the field knows about the role culture plays in online learning. Further, the question is situated in the interplay between online learning behaviors influenced by Confucius culture and Western teaching pedagogy. The shared understandings of Confucius culture and Western culture presented in current literature are reviewed and compared. The impact on online learning beliefs and behaviors of international student sojourners from Confucius culture is discussed from the following three dimensions: teacher-student relationship, curriculum development, and teaching and learning pedagogy. This study cautions that culture matters in online learning but its influence should neither be underestimated nor overestimated/stereotyped.
Keywords: Online learning behaviors; Online learning beliefs; Western culture; Confucius culture; International students; Teacher-student relationships; Curriculum development; Teaching and learning pedagogy